VIRTUAL ETNOGRAPHY (Kajian Etnografi Komunikasi pada Media Sosial Facebook di Indonesia) - Prasetya, Hendri (Universitas Prof. Dr. Moestopo (Beragama), 2013)
This research attempt to explain a social technological aspect of a new media social network sites which basedon a individual subjective meaning about Computer Mediated Communication as a social activity. Constructionof meaning that build within the user provide a set of value and shared meaning that creates a set of behavior,including communication behavior especially the language that employed among the user. The user also usedlanguage as a symbolic meaning through social network sites facebook to creates and managing self identity.The research used a qualitative approach with communication etnographic approach. Informant wre selectedbased on purposive. The data collected through participant observation, interviews and document searches. Theresult showed a different set of meaning of CMC activity among the user that also creates a different use pattern.A degree of enggagement creates a different set of communication bahavior based on maps of meaning and setof norm that created among those virtual community and also described abou self identity management betweenuser.